2021
DOI: 10.31729/jnma.6487
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in Patient with Abnormal Uterine Bleeding in a Tertiary Hospital of Eastern Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Thyroid hormone is known to affect reproductive biology. Abnormal uterine bleeding is one of the common presentations in gynaecology outpatient departments and thyroid dysfunction is known to affect its progression. This study aims to find the prevalence of thyroid dysfunction in diagnosed cases of abnormal uterine bleeding in patients in a tertiary hospital of eastern Nepal. Methods: A descriptive cross-sectional study was conducted in patients diagnosed with abnormal uterine bleeding in a terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…AUB and hypothyroidism. Result of this study is similar to the results of many previous studies13,14 . Whitaker et al, documented the hypothyroidism is one of the common diseases that must be assessed among women with abnormal uterine bleeding 2 .…”
supporting
confidence: 92%
See 1 more Smart Citation
“…AUB and hypothyroidism. Result of this study is similar to the results of many previous studies13,14 . Whitaker et al, documented the hypothyroidism is one of the common diseases that must be assessed among women with abnormal uterine bleeding 2 .…”
supporting
confidence: 92%
“…The mean age of the patients was 33±8 years. Among thyroid dysfunction, 9 (60.0%) were hypothyroid, 4 (26.66 %) were subclinical hypothyroid, and 2 (13.33 %) were hyperthyroid 13 . Another study reported thyroid disorders are common in females with subclinical hypothyroidism as it's the most common type.…”
Section: Introductionmentioning
confidence: 99%
“…As Kakatiya Medical College and MGM Hospital in Warangal are government institutions, this funding ensured that all participants received the necessary thyroid function tests at no personal expense, facilitating thorough data collection and analysis for the study. The reference ranges for thyroid hormone levels were defined according to established American Thyroid Association (ATA) clinical guidelines [1,4,[8][9][10]. For TSH, the ranges are as follows: Low: <0.4 mIU/L, Normal: 0.4-4.0 mIU/L, and High: >4.0 mIU/L.…”
Section: Thyroid Function Testsmentioning
confidence: 99%
“…Hyperthyroidism is a condition that occurs when thyroid-stimulating hormone level is low with free T3 and T4 levels are high (13) . The association of hyperthyroidism with amenorrhea has been described as early as 1840 by Von Bosedow (14) . Subclinical hyperthyroidism is defined by a low serum thyroid-stimulating hormone concentration, with normal free T3 and T4 concentrations (15,16) .…”
Section: Introductionmentioning
confidence: 99%